Low Temperature Synthesis of TiO2 Nanoparticles with High Photocatalytic Activity and Photoelectrochemical Properties through Sol–Gel Method. Issue 2 (25th January 2016) - Bazrafshan, Hamed; Alipour Tesieh, Zahra; Dabirnia, Saeideh; Naderifar, Abbas
Abstract : In the present work TiO2 nanoparticles were prepared by sol–gel method and both small-sized nanoparticles and proper crystals were delivered by simultaneous use of surfactant, which was applied for the purpose of size reduction of nanoparticles, and acid ions that were used so that the formation of crystalline structures occurs appropriately. Photocatalytic activity of samples was measured by degrading RO dye, and photoelectrochemical properties were assayed using anodic photocurrent responses under Xe lamp light irradiation. The synthesized nanoparticles exhibit great photoelectrochemical and photocatalytic activity compared to that of commercial photocatalyst, Degussa P-25, which demonstrates that the method can be applied in the synthesis of other semiconductor oxides nanoparticles.